Assessing Normandy Soil Microbial Diversity for Antibacterial Activities Using Traditional Culture and iChip Methods - Fabien Perrier; Juliette Morice; Sabrina Gueulle; Antoine Géry; Eliette Riboulet-Bisson; David Garon; Cécile Muller; Florie Desriac (Microorganisms)
Uncultured microorganisms represent a promising and untapped source of antibacterial compounds, crucial in the fight against the significant threat of antimicrobial resistance (AMR). In this study, both traditional and isolation chip (iChip) cultivation techniques were employed to enhance the recovery of known and unknown microorganisms from soils located in Normandy, France. The isolates obtained were identified using 16S rDNA or ITS regions analysis and MALDI-TOF mass spectrometry and were screened for antibacterial activity. A total of 386 isolates, belonging to 6 microbial phyla and distributed across 65 genera, were recovered using both methods. In total, 11 isolates are potentially new bacterial species, and 34 were associated with 22 species described recently. The iChip method yielded a higher diversity of microorganisms (47 genera) than the traditional method (38 genera) and was particularly effective in enriching Actinomycetota. Antibacterial screening against target bacteria showed that 85 isolates (22%) exhibited antibacterial activity. The Streptomyces, Pseudomonas, and Bacillaceae taxa accounted for most antibacterial-producing bacteria with some presenting promising undescribed characteristics. Other active isolates were affiliated with less-known antibacterial producers such as Arthrobacter, Chryseobacterium, Delftia, Ensifer, Flavobacterium, Rahnella, and Stenotrophomonas, among others. These results highlight the potential of our microbial collection as a source of new antibacterial natural products.